ANALISIS PENGARUH BIAYA LOGISTIK TERHADAP NILAI DISTRIBUSI IKAN KONSUMSI - Pelamonia, Julie Th.; Farida, Titik Nur (Journal of Applied Accounting, 2023)
The purpose of this study is to analyze the influence of logistic cost toward distribution value of consumption fish of Pelabuhan Perikanan Nusantara Ambon. This study used secondary data in the form of time series data from January 2016 to December 2020. Data analysis method usedin this research is multiple linear regression equipped with a descriptive analysis, a classic assumption test and hypothesis testing. The classic assumption test shows that there is no problem with the variable being tested. The F-Test shows that logistic cost simultaneously and significantly influence distribution value of consumption fish. The T- test shows that logistic cost have a negative and significant effect toward distribution value of consumption fish. Based on the coefficient of determination, the logistic cost have an effect of 49.2% on the distribution value of consumption fish of Pelabuhan Perikanan Nusantara Ambon while the remaining 50.8% is influenced by other variables outside this study. Keywords: logistics costs, distribution value of consumption fish